Students' Lexical Difficulties in Classical Mechanics and Modern Physics Vocabulary: A Survey Analysis - Falakh, Athfatullaila; Widana, Sausan Nada; Sidik, Muhamad Raka Arya; Wahyunengsih, Wahyunengsih (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study is to map undergraduate students’ physics vocabulary needs in classical mechanics and modern physics by identifying their levels of familiarity, frequency of use, and perceived difficulty of scientific terms across different physics domains. Methodology: This study employed a descriptive quantitative survey method. The instrument was a researcher-developed structured questionnaire containing physics vocabulary items, validated by expert review. Data were collected online using Google Forms. Responses were measured with a three-point Likert scale and analyzed descriptively using Microsoft Excel software. Main Findings: The results show that students demonstrate high vocabulary recognition in classical mechanics and energy-related terms. Moderate recognition appears in laboratory and academic vocabulary. Low recognition is found in thermodynamics and modern physics terms, especially abstract and theoretical concepts. Overall vocabulary familiarity decreases as conceptual abstraction increases across physics domains. Novelty/Originality of this study: This study introduces a systematic, domain-based mapping of physics vocabulary by integrating familiarity, frequency of use, and perceived difficulty across multiple physics fields. It advances existing research by providing comparative evidence between classical mechanics and modern physics, offering empirical insights that support targeted vocabulary instruction in higher education physics learning.